The Influence of Mobile Learning Apps on Children’s Cognitive Development - Marcus Yong Wei; Lucas Han Ming (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
Mobile learning apps have gained popularity as an educational tool for children, offering an interactive and engaging approach to learning. This paper explores the influence of mobile learning apps on children's cognitive development, focusing on skills such as memory, problem-solving, and attention. The study reviews several mobile learning applications used in early childhood education and assesses their effectiveness in fostering cognitive growth and skill development.